Conditions associated with sarcopenia and sarcopenic obesity among community-dwelling older people (Research, Society and Development, 2021)
Objective: to investigate the factors associated with sarcopenia and sarcopenic obesity (SO) in community-dwelling older people. Methods: This was a cross-sectional community-based study. Sarcopenia was diagnosed according to the cutoff points of hand grip strength (HGS), and SO was identified through a low HGS concomitant with a high body fat percentage, according to sex, determined using electrical bioimpedance. Calorie and protein intake was estimated using a 24-hour recall. Socio-demographic data were obtained by means of an interview and the level of physical activity was assessed using a specific instrument. Results: Prevalence of 43% and 19.6% were observed for sarcopenia and SO, respectively. Older people aged ≥ 70 years have a significantly higher risk for sarcopenia in 183% (PR = 2.83; 95% CI = [1.62 to 4.96]; p value < 0.001) compared to those aged 60 to 69 years. The prevalence of sarcopenia was higher in males, among those who contribute to family support, present comorbidities and are less physically active. The prevalence of SO and sarcopenia was high, but this study did not allow us to observe statistically significant associations. Calorie and protein intakes were predominantly inadequate throughout the sample, however, there was no association with sarcopenia and SO. Conclusion: Advance years of life was shown to be a factor associated with sarcopenia, and with SO. Contributing to family support and insufficient physical activity were determining conditions for the occurrence of sarcopenia.